The presence and prediction of lateralized inattention 7 years post‐stroke. (22nd January 2020) - Gerafi, Joel; Samuelsson, Hans; Viken, Jo I.; Jern, Christina; Blomstrand, Christian; Jood, Katarina
Abstract : Objective: Lateralized inattention is a typical sign of neglect and related to poor functional outcome. Knowledge of the long‐term course of this phenomenon is limited. The purpose of this study was to investigate presence and predictors for signs of lateralized inattention 7 years after stroke. Methods: From a cohort of acute ischemic stroke patients, aged 18‐69 years ( n  = 297), a consecutive series of 188 survivors without recurrent stroke at follow‐up 7 years later were included. Within the first week after stroke onset, stroke severity was assessed according to the Scandinavian Stroke Scale. Target omissions, asymmetry of omissions, and perceptual speed according to Star‐ and Letter Cancellation Tests were also assessed. Presence of lateralized inattention at the 7‐year follow‐up was investigated with the Star‐ and Letter Cancellation Tests and with the neglect item in the National Institutes of Health Stroke Scale. Results: At the follow‐up, 22 (11.7%) participants had lateralized inattention and the multivariable regression showed that independent significant baseline predictors were total omissions in target cancellations ( P  < .001) and inferior baseline performance on visual processing speed ( P  = .008). Conclusion: About one of ten individuals exhibited signs of lateralized inattention 7 years after stroke. Baseline performance in perceptual processing speed and target omissions independently predicted presence of late signs of lateralized inattention. This is the first time processing speed is recognized as a significant predictor of lateralized inattention several years after the stroke incidence, indicating that the longitudinal course of processing speed following stroke is a critical subject for future research.